2020
DOI: 10.1111/apt.15789
|View full text |Cite
|
Sign up to set email alerts
|

Sequential systemic treatment in patients with hepatocellular carcinoma

Abstract: Summary Background Hepatocellular carcinoma (HCC) is one of the most lethal cancers. After many years of stagnation, there are now several systemic treatments available for patients with HCC. Aim To analyse the feasibility and efficacy of sequential systemic treatments in patients with HCC in clinical practice. Methods In this multicentre study, patients who were treated with novel systemic therapies for HCC between 2014 and 2019 at two referral centres, Hannover Medical School, Germany, and Medical University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 23 publications
3
24
0
Order By: Relevance
“…With 17.1% of all initial treatment modalities, our proportion of systemic therapy maintained unchanged compared to the cohort of Kirstein et al and lies within the range of the BRIDGE trial (Kirstein et al 2017;Park et al 2015). In alignment with a recently published sequence analysis of systemic therapies, the most common 1 st line treatment was sorafenib with 83.5% (Kirstein et al 2020). However, this might change with the combinatory treatment of atezolizumab and bevacizumab (Finn et al 2020).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…With 17.1% of all initial treatment modalities, our proportion of systemic therapy maintained unchanged compared to the cohort of Kirstein et al and lies within the range of the BRIDGE trial (Kirstein et al 2017;Park et al 2015). In alignment with a recently published sequence analysis of systemic therapies, the most common 1 st line treatment was sorafenib with 83.5% (Kirstein et al 2020). However, this might change with the combinatory treatment of atezolizumab and bevacizumab (Finn et al 2020).…”
Section: Discussionsupporting
confidence: 53%
“…Clinical decision making is guided by interdisciplinary tumor boards, yet selecting the most favorable option, especially in sequential therapies across different disease stages, remains challenging (Allaire and Nault 2017;Kirstein et al 2020Kirstein et al , 2017. Therapeutic stratification of HCC patients is conducted by imaging, clinical criteria and the extent of liver function assessed most commonly by the Barcelona Clinic Liver Cancer (BCLC) classification, the Eastern Cooperative Oncology Group (ECOG) performance status and the Child-Pugh score (Forner et al 2009;Hinrichs et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies from outside Japan show similar results. A study of patients who underwent multi-drug sequential therapy between 2014 and 2019 reported a median OS of 35 months, and patients received up to 5 lines of therapy [19]. In this study, lenvatinib was also frequently used as second-line (12.9%) and third-line (10.5%) therapy.…”
Section: Multi-drug Sequential Therapymentioning
confidence: 89%
“…As a fact, lenvatinib (a TKI targeting VEGFR) became an effective alternative to sorafenib as first-line therapy for HCC in 2018, while regorafenib, cabozantinib, and ramucirumab only recently have been approved in the second-line setting [ 8 ]. With the advent of second-line treatments, the survival of patients with advanced HCC has significantly improved, with a proportion (approximately 20%) of patients reaching survival times of about 2 years with the sequential use of sorafenib-regorafenib [ 9 ]. These patients, however, belong to a small subgroup of patients who, maintaining an optimal liver function, are eligible for sequential treatment and tolerate the adverse effects of the anti-neoplastic agents [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of second-line treatments, the survival of patients with advanced HCC has significantly improved, with a proportion (approximately 20%) of patients reaching survival times of about 2 years with the sequential use of sorafenib-regorafenib [ 9 ]. These patients, however, belong to a small subgroup of patients who, maintaining an optimal liver function, are eligible for sequential treatment and tolerate the adverse effects of the anti-neoplastic agents [ 9 ].…”
Section: Introductionmentioning
confidence: 99%